Attaining the 2030 Sustainable Development Goal of Industry, Innovation and Infrastructure - Birdthistle, Naomi, editor 646771; Hales, Rob, editor 646772; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2020)
Attaining the 2030 Sustainable Development Goal of Industry, Innovation and Infrastructure examines family businesses in Algeria, Japan, Australia and Germany, analysing how the SDG9 translates into family businesses and providing insights into how businesses can advance innovation, industrialisation and robust infrastructure.